The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.ijpsycho.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlates of the development of theta event related oscillations in adolescents and young adults

Abstract: The developmental trajectories of theta band (4–7 Hz) event-related oscillations (EROs), a key neurophysiological constituent of the P3 response, were assessed in 2170 adolescents and young adults ages 12 to 25. The theta EROs occurring in the P3 response, important indicators of neurocognitive function, were elicited during the evaluation of task-relevant target stimuli in visual and auditory oddball tasks. Associations between the theta EROs and genotypic variants of 4 KCNJ6 single nucleotide polymorphisms (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 126 publications
(198 reference statements)
3
24
0
Order By: Relevance
“…From these data, we conclude that measures of neural connectivity can be used to further understanding of how polygenic liability to AD may influence brain function, as well as the importance of examining sex and developmental effects in polygenic associations. We note however, that effect sizes were modest, ranging between 0.15 and 0.21 (beta coefficients ranged from 0.02–0.06), consistent with other developmental studies of EEG phenotypes [54,58].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…From these data, we conclude that measures of neural connectivity can be used to further understanding of how polygenic liability to AD may influence brain function, as well as the importance of examining sex and developmental effects in polygenic associations. We note however, that effect sizes were modest, ranging between 0.15 and 0.21 (beta coefficients ranged from 0.02–0.06), consistent with other developmental studies of EEG phenotypes [54,58].…”
Section: Discussionsupporting
confidence: 89%
“…Association of PRS with EEG coherence trajectories were calculated as described in detail in Chorlian et al [54]. Briefly, to test for association between each PRS and EEG coherence phenotype (27 coherence pairs, 7 frequency bands, 3 PRS levels), a local linear (non-parametric) regression model was calculated, including the PRS as the predictor and the inverse hyperbolic tangent of the coherence measure as the dependent variable.…”
Section: Methodsmentioning
confidence: 99%
“…Pandey et al, 2012). Recent genetic studies and the current study have demonstrated associations of KCNJ6 with theta EROs (Kang et al, 2012; Chorlian et al, in press). The current study has indicated that variations in the KCNJ6 SNP (rs702859) influence magnitude of theta ERO power at posterior leads during during the evaluation of loss and gain, reflecting a genetic influence on neuronal circuits involved in reward processing.…”
Section: Discussionsupporting
confidence: 53%
“…Kang et al, 2012). Following up this finding, a recent study from our group examined the effects of KCNJ6 SNPs on developmental trajectories of the same theta ERO phenotypes in auditory and visual oddball tasks in adolescent and young adults (12–25) from the COGA prospective study; significant age- and gender-specific effects were found, with some effects of scalp locality and task modality (Chorlian et al, in press). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation